The role of CEP164 in ciliogenesis in Drosophila melanogaster - Rocha, Jaqueline Maria Matias da (2018)
Cilia/flagella are microtubule (MT)-based oraganelle emanating from the surface of many eukaryotic cells. They are involved in a variety of processes including cell motility, fluid flow, and sensing processes. The skeleton of cilium, called axoneme, is templated from the basal body, a modified mature centriole required for centrosome formation. Mutations in human genes disrupting the function or structure of these organelles cause several human disorders, including infertility, ciliopathies, and cancer. In Drosophila melanogaster, cilia are present in the neurons and in the sperm. Defects in these structures and/or in its functions lead to clear phenotypes, such as delayed development, uncoordination and sterility. CEP164, a centrosomal protein, localizes at the distal appendages of the mature centriole. Mutations in CEP164 gene, in humans, cause Nephronophthisis, a ciliopathy that causes organ degeneration. The aim of this work consists of studying the CEP164 role in ciliogenesis and cilia function in sensory neurons and sperm in D. melanogaster. For that, we used two strategies: one involving knock down of CEP164 in neurons and sperm using the Gal4/UAS system, and other the generation of new excition alleles of CEP164 to study the effect of CEP164 in the fruit fly. In D. melanogaster olfactory neurons, CEP164 localizes at the connceting cilia, a transition zone equivalent structure. We observed by RNAi knock down that CEP164 is important for adult fly proper coordination. The cilia structures were affected in those flies, however, the fertility of those males was not affected.